Comparison of isokinetic knee torque and bioelectrical activity for hamstrings, quadriceps and erector spinae muscles in elite rowers - Kabacinski, J.; Fryzowicz, A.; Blaszczyk, A.; Murawa, M.; Gorwa, J.; Ogurkowska, M. B. (Sports Biomechanics, 2022)
In sweep rowers, the lower extremities muscle strength translates into the driving force of the boat. Therefore, isokinetic assessment of muscle torque is used by coaches as an indicator of the level of athletes` preparation for competitions. A total of 22 elite sweep rowers performed an isokinetic test of knee joint flexors and extensors, and a test on an asymmetric ergometer with the electromyography measures. Significantly higher quadriceps peak torque was shown during the beginning than the end of the preparatory period (p < 0.05). However, there was no significant knee peak torque difference between the lower extremities (p = 0.398). In the case of the electromyography test of quadriceps, hamstrings and lumbar erector spinae, analysis demonstrated significant bioelectrical activity differences between the sides (p < 0.05). Lower values of quadriceps peak torque at the end of the preparatory period may result from a decrease in the number of power training units during the entire preparatory period. A similar muscle strength between both lower extremities seems to be the correct result in the context of injury prevention. In turn, significant bioelectrical activity differences between the sides possibly are associated with the asymmetric movement pattern in sweep rowers.